Categories in Hegel: Logic, Metaphysics, and Method (Revista Eletrônica Estudos Hegelianos, 2025)
The article investigates the problem of categories within the philosophical tradition, with Hegel’s Science of Logic as its point of arrival. To situate its specificity, we analyze the treatment of categories in Aristotle and Kant, considering in each author the definition of the concept of category, the method employed in its deduction, and the relation established between logic and metaphysics. We show how, in Hegel, the issue undergoes a decisive reformulation: the ordering of categories is not conceived as an arbitrary list nor as a mere condition of possibility of experience, but as the immanent development of thought, in which logic and metaphysics coincide. The study thus seeks to highlight how the Hegelian dialectical method responds to the problem of the scientific character of philosophy, articulating the categorial deduction with the identity of being and thought.